Peripheral Blood Mucosal-Associated Invariant T Cells in Tuberculosis Patients and Healthy Mycobacterium tuberculosis-Exposed Controls. (8th April 2020) - Suliman, Sara; Gela, Anele; Mendelsohn, Simon C; Iwany, Sarah K; Tamara, Kattya Lopez; Mabwe, Simbarashe; Bilek, Nicole; Darboe, Fatoumatta; Fisher, Michelle; Corbett, Alexandra J; Kjer-Nielsen, Lars; Eckle, Sidonia B G; et al.
Abstract: Background: In human blood, mucosal-associated invariant T (MAIT) cells are abundant T cells that recognize antigens presented on non-polymorphic major histocompatibility complex-related 1 (MR1) molecules. The MAIT cells are activated by mycobacteria, and prior human studies indicate that blood frequencies of MAIT cells, defined by cell surface markers, decline during tuberculosis (TB) disease, consistent with redistribution to the lungs. Methods: We tested whether frequencies of blood MAIT cells were altered in patients with TB disease relative to healthy Mycobacterium tuberculosis -exposed controls from Peru and South Africa. We quantified their frequencies using MR1 tetramers loaded with 5-(2-oxopropylideneamino)-6-D-ribitylaminouracil. Results: Unlike findings from prior studies, frequencies of blood MAIT cells were similar among patients with TB disease and latent and uninfected controls. In both cohorts, frequencies of MAIT cells defined by MR1-tetramer staining and coexpression of CD161 and the T-cell receptor alpha variable gene TRAV1-2 were strongly correlated. Disease severity captured by body mass index or TB disease transcriptional signatures did not correlate with MAIT cell frequencies in patients with TB. Conclusions: Major histocompatibility complex (MHC)-related 1-restrictied MAIT cells are detected at similar levels with tetramers or surface markers. Unlike MHC-restricted T cells, blood frequencies of MAIT cells are poor correlates of TB disease but may play a role in pathophysiology.